Ekspor teknologi tinggi, PMA dan pengendalian korupsi dalam dinamika kompleksitas ekonomi Indonesia - Rona Hinirim Gultom; Joko Suharianto (Journal of Economics Research and Policy Studies, 2026)
This research explores the determinants shaping Indonesia's economic complexity index between 1998 and 2024, specifically examining three critical variables: technologically advanced product exports, incoming foreign capital investments, and governmental anti-corruption measures. Employing a quantitative analytical framework, the study utilizes secondary time-series data analyzed through the Error Correction Model methodology, enabling distinction between immediate and sustained economic dynamics. Empirical findings reveal nuanced patterns across different temporal horizons. Technologically sophisticated exports demonstrate statistically insignificant immediate effects but emerge as robust positive contributors over extended periods. Foreign capital inflows, conversely, exhibit no meaningful statistical association with the complexity index across both short-term and long-term frameworks. Anti-corruption governance initiatives consistently prove their significance, displaying positive statistical relationships regardless of temporal scope. The collective analytical power of these three determinants demonstrates substantial explanatory capacity, jointly accounting for significant variations in Indonesia's economic complexity measurement across both analytical timeframes. These results underscore the differential temporal impacts of technological advancement, capital mobility, and institutional quality on economic sophistication within developing economies.